Epoxy resin composition, cured product, and semiconductor device

A tailored epoxy resin composition with surface-treated inorganic filler and hydrophobized cellulose nanofibers addresses the toughness and thermal expansion issues in semiconductor encapsulation, enhancing thermal cycle resistance and reducing cracks in semiconductor devices.

JP2025005765APending Publication Date: 2025-01-17NAMICS CORPORATION
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023106105
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing epoxy resin compositions used in semiconductor encapsulation lack sufficient toughness and thermal expansion properties, leading to cracks in bump electrodes due to thermal cycling.

Method used

An epoxy resin composition containing a specific blend of epoxy resin, hardening agent, surface-treated inorganic filler, and cellulose nanofibers, with controlled fiber width and hydrophobicity, to achieve low thermal expansion and high toughness.

Benefits of technology

The composition results in a cured product with improved thermal cycle resistance, reducing cracks in semiconductor devices and enhancing the durability of bump electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005765000001
    Figure 2025005765000001
Patent Text Reader

Abstract

To provide an epoxy resin composition that yields a cured product with low thermal expansion and high toughness and also to provide a semiconductor device that comprises a cured product with low thermal expansion and high toughness.SOLUTION: An epoxy resin composition contains an epoxy resin (A), a curing agent (B), a surface-treated inorganic filler (C), and a cellulose nanofiber (D).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin composition, and more specifically to an epoxy resin composition for semiconductor encapsulation, a cured product, and a semiconductor device. [Background technology]

[0002] As electronic devices become smaller, lighter, and more powerful, the mounting format of semiconductors is changing from wire bond type to flip chip type. Flip chip type semiconductor devices have a structure in which electrodes on a substrate are connected to a semiconductor element via bump electrodes. When heat is applied to such semiconductor devices, the difference in thermal expansion coefficient between the substrate and the semiconductor element causes stress to be applied to the bump electrodes, which causes defects such as cracks in the bump electrodes.

[0003] In order to prevent such defects, a semiconductor sealant called underfill is widely used. Underfill is a liquid sealant that is injected into the gap between the semiconductor element and the substrate and then thermally cured to fix the semiconductor element and the substrate together, thereby improving thermal cycle resistance. In addition, a method for further improving thermal cycle resistance is known in which an inorganic filler is added to the semiconductor sealant to reduce the thermal expansion coefficient of the cured product (sealant).

[0004] Epoxy resins are known as resins used in semiconductor encapsulants. Semiconductor encapsulants containing epoxy resins tend to be brittle when cured, and cracks are likely to occur due to stress from thermal cycles and the like. Therefore, strengthening the toughness of the cured product is effective from the viewpoint of improving thermal cycle resistance. Cellulose nanofibers (CNF) are also known as materials that impart low thermal expansion to the cured product (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-077762 A [Patent Document 2] JP 2012-177012 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the toughness imparted to the cured product by blending such cellulose nanofibers cannot be said to be sufficient.

[0007] Therefore, an object of the present invention is to provide an epoxy resin composition which gives a cured product having low thermal expansion and high toughness, and to provide a semiconductor device provided with the cured product having low thermal expansion and high toughness. [Means for solving the problem]

[0008] As a result of intensive research conducted by the present inventors to achieve the above object, it was found that a cured product of an epoxy resin composition containing a specific component has both low thermal expansion and high toughness properties. The present invention was completed based on these findings.

[0009] That is, in the present invention, Epoxy resin (A), Hardener (B), A surface-treated inorganic filler (C), and Cellulose nanofiber (D), The epoxy resin composition includes:

[0010] The average fiber width of the cellulose nanofibers (D) is preferably 1 to 1000 nm.

[0011] The cellulose nanofibers (D) are preferably hydrophobized cellulose nanofibers.

[0012] The inorganic filler (C) is preferably an inorganic filler having an epoxy group, a (meth)acryloyl group, or a substituted or unsubstituted amino group.

[0013] The inorganic filler (C) preferably contains an inorganic filler (C-1) having an average particle size of 1 to 100 nm and an inorganic filler (C-2) having an average particle size of 0.2 to 8 μm.

[0014] The content of the cellulose nanofibers (D) is preferably 0.1 to 10.0% by mass relative to the epoxy resin composition (100% by mass).

[0015] The above epoxy resin composition preferably further contains a reactive diluent (E).

[0016] The epoxy resin composition preferably has a viscosity at 25°C of 1 to 80 Pa·s.

[0017] The above epoxy resin composition is preferably used for semiconductor encapsulation.

[0018] The present invention also provides a cured product of the above epoxy resin composition.

[0019] The present invention also provides a semiconductor device including a substrate, a semiconductor element disposed on the substrate, and the cured product that encapsulates the semiconductor element. Effect of the Invention

[0020] According to the epoxy resin composition of the present invention, a cured product having both low thermal expansion and high toughness can be obtained. Therefore, when the epoxy resin composition is used for semiconductor encapsulation, the thermal cycle resistance of the semiconductor device is improved and the occurrence of cracks in the cured product, semiconductor element, bump electrode, etc. is reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] <Epoxy resin composition> The present invention relates to an epoxy resin composition comprising an epoxy resin (A), a curing agent (B), a surface-treated inorganic filler (C), and a cellulose nanofiber (D). Hereinafter, the surface-treated inorganic filler (C) may be simply referred to as "inorganic filler (C)".

[0022] [Epoxy resin (A)] The epoxy resin composition of the present invention can form a cured product with high electrical insulation by including the epoxy resin (A). The epoxy resin (A) is not particularly limited, but examples thereof include aromatic epoxy resins and aliphatic epoxy resins. The number of epoxy groups in the epoxy resin (A) is not particularly limited as long as it is 1 or more, but from the viewpoint of reliability such as thermal cycle resistance, it is preferably 2 or more (i.e., it is a multifunctional epoxy resin). The number of epoxy groups in the epoxy resin (A) is not particularly limited, but is preferably 5 or less, for example. The epoxy resin (A) can be used alone or in combination of two or more.

[0023] The epoxy resin (A) may be liquid or solid, but is preferably liquid from the viewpoint of the viscosity of the epoxy resin composition. The epoxy resin (A) is a compound containing an epoxy group, exemplified as the reactive diluent (E) described later, excluding compounds having a molecular weight of 350 or less.

[0024] The epoxy resin (A) may be a petroleum-derived epoxy resin or a non-petroleum-derived epoxy resin. Specific examples of the non-petroleum-derived epoxy resin include plant-derived epoxy resins. In the plant-derived epoxy resin, biomass such as fats and oils can be used as the plant raw material. Examples of the fats and oils include olive oil, soybean oil, rapeseed oil, sesame oil, linseed oil, sunflower oil, castor oil, corn oil, cashew oil, palm oil, etc. In addition, lignin obtained from plants such as wood (coniferous trees, broad-leaved trees, etc.) and rice can be used as biomass other than fats and oils. That is, epoxy resins obtained by modifying or denaturing the lignin can also be used as plant-derived epoxy resins.

[0025] The aromatic epoxy resin is not particularly limited as long as it is an epoxy resin having a structure containing an aromatic ring such as a benzene ring, but examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, fluorene type epoxy resin, biphenyl aralkyl epoxy resin, diepoxy resin such as 1,4-phenyldimethanol diglycidyl ether, biphenyl type epoxy resin such as 3,3',5,5'-tetramethyl-4,4'-diglycidyloxybiphenyl, diglycidyl aniline, diglycidyl toluidine, tetraglycidyl-m-xylylenediamine, glycidyl amine type epoxy resin, triglycidyl-p-aminophenol, and naphthalene ring-containing epoxy resin. Among them, glycidyl amine type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, aminophenol type epoxy resin, and naphthalene ring-containing epoxy resin are preferred.

[0026] The aliphatic epoxy resin is not particularly limited, and examples thereof include diepoxy resins such as ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-hexanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, glycerin diglycidyl ether, neopentyl glycol diglycidyl ether, polyethylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether (particularly, mono- or polyalkylene glycol-type diepoxy resins); trimethylolpropane triglycidyl ether, Examples of epoxy resins include triepoxy resins such as vinyl(3,4-cyclohexene) dioxide and glycerin triglycidyl ether; alicyclic epoxy resins such as vinyl(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-m-dioxane; glycidylamine-type epoxy resins such as tetraglycidyl bis(aminomethyl)cyclohexane; hydantoin-type epoxy resins such as 3-diglycidyl-5-methyl-5-ethylhydantoin; and epoxy resins having a silicone skeleton such as 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane. Among these, monoalkylene glycol-type diepoxy resins such as ethylene glycol diglycidyl ether, 1,4-hexanediol diglycidyl ether, and 1,4-butanediol diglycidyl ether, and polyalkylene glycol-type diepoxy resins such as polytetramethylene glycol diglycidyl ether and polyethylene glycol diglycidyl ether are preferred.

[0027] The epoxy equivalent of the epoxy resin (A) is not particularly limited, but is, for example, preferably 30 to 1500 g / eq, more preferably 60 to 1000 g / eq, and further preferably 80 to 800 g / eq.

[0028] The content of the epoxy resin (A) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is, for example, preferably 3 to 80% by mass, more preferably 5 to 60% by mass, further preferably 8 to 50% by mass, and particularly preferably 12 to 40% by mass. When the content of the epoxy resin (A) is within the above range, the thermal expansion of the cured product tends to be reduced and the toughness tends to be improved. In addition, the viscosity of the epoxy resin composition tends to be reduced.

[0029] [Hardening agent (B)] The curing agent (B) is not particularly limited as long as it initiates, advances, or accelerates the polymerization of the epoxy resin, and examples thereof include amine-based curing agents, acid anhydride-based curing agents, phenol-based curing agents, and imidazole-based curing agents. The curing agent (B) may be used alone or in combination of two or more.

[0030] Examples of the amine-based curing agent include aromatic amines such as 4,4'-diamino-3,3'-diethyldiphenylmethane, diethyltoluenediamine, dimethylthiotoluenediamine, methylenedianiline, m-phenylenediamine, 4,4'-diaminodiphenylsulfone, and 3,3'-diaminodiphenylsulfone. Examples of the acid anhydride-based curing agent include alkylated tetrahydrophthalic anhydrides such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, phthalic anhydride, dodecenyl succinic anhydride, and methylnadic anhydride. Examples of the phenol-based curing agent include phenol novolac resin, cresol novolac resin, naphthol-modified phenolic resin, dicyclopentadiene-modified phenolic resin, and p-xylene-modified phenolic resin. Examples of the imidazole-based hardener include 2-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-imidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Examples of the imidazole-based hardener include microcapsule-type imidazole-based hardener.

[0031] The equivalent weight (molecular weight per functional group) of the curing agent (B) is not particularly limited, but is, for example, preferably 20 to 600 g / eq, more preferably 30 to 400 g / eq, and further preferably 40 to 200 g / eq.

[0032] The content of the curing agent (B) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is, for example, preferably 0.1 to 60% by mass, more preferably 0.3 to 50% by mass, further preferably 0.5 to 40% by mass, and particularly preferably 1 to 30% by mass. By having the content of the curing agent (B) within the above range, the thermal expansion of the cured product tends to be reduced and the toughness tends to be improved.

[0033] [Inorganic filler (C)] The inorganic filler (C) is not particularly limited as long as it is surface-treated, but it is preferable that it has a property of suppressing the volumetric shrinkage (cure shrinkage) caused by the curing reaction of the epoxy resin composition, a property of reducing the thermal expansion of the cured product, or both of these properties. Since the inorganic filler (C) is surface-treated, it tends to be able to impart high toughness to the cured product, and the viscosity of the epoxy resin composition is significantly reduced, so that the problem of speed reduction during injection into the gap tends to be less likely to occur.

[0034] Examples of the inorganic filler (C) include surface-treated inorganic particles such as silica, silicon carbide, silicon nitride, alumina (aluminum oxide), aluminum nitride, aluminum hydroxide, aluminum silicate, magnesium silicate, calcium silicate, calcium carbonate, barium sulfate, barium carbonate, titanium oxide, lime sulfate, potassium titanate, magnesium carbonate, zinc oxide, boron nitride, and zirconia (zirconium oxide). From the viewpoint of increasing the loading amount, it is preferable to use silica as the inorganic particles. The inorganic filler (C) can be used alone or in combination of two or more kinds.

[0035] From the viewpoint of imparting high toughness to the cured product while reducing the viscosity of the epoxy resin composition, the inorganic filler (C) preferably has an epoxy group, a (meth)acryloyl group, or a substituted or unsubstituted amino group as a functional group. In other words, the inorganic filler (C) is preferably surface-treated with a coupling agent having an epoxy group, a (meth)acryloyl group, or a substituted or unsubstituted amino group. The inorganic filler (C) may have only one type of the functional group, or may have two or more types. Examples of the substituted or unsubstituted amino group include an amino group; mono- or di-alkylamino groups such as a methylamino group, an ethylamino group, an isopropylamino group, a dimethylamino group, and a diethylamino group; and an arylamino group such as a phenylamino group. Among these, the substituted or unsubstituted amino group is particularly preferably a phenylamino group.

[0036] The inorganic filler (C) is preferably one that has been surface-treated with a silane coupling agent. By performing surface treatment with a silane coupling agent, the viscosity of the epoxy resin composition tends to be reduced.

[0037] The integral blend method is known as a method of directly blending a surface treatment agent such as a coupling agent into an epoxy resin composition. When an epoxy resin composition contains an inorganic filler that has not been surface-treated and a surface treatment agent such as a coupling agent, the inorganic filler may be surface-treated with the surface treatment agent in the epoxy resin composition. In the epoxy resin composition of the present invention, the inorganic filler (C) may be surface-treated by the integral blend method, but it is preferable that the inorganic filler is surface-treated in advance. That is, the epoxy resin composition of the present invention is preferably obtained by mixing a component such as an epoxy resin (A) with a surface-treated inorganic filler (C).

[0038] In the integral blend method, the surface treatment agent is directly blended into the epoxy resin composition, and the surface treatment agent may react with components other than the inorganic filler (e.g., epoxy resin (A), curing agent (B), and cellulose nanofiber (D), etc.), resulting in an increase in the viscosity of the epoxy resin composition and making it difficult to adjust. In addition, the intended inorganic filler (C) may not be sufficiently formed in the epoxy resin composition, or even if it is formed, the surface of the inorganic filler may not be sufficiently treated. In comparison, when an inorganic filler (C) that has been surface-treated in advance is used, the viscosity of the epoxy resin composition can be easily adjusted, and the problem of speed reduction during injection into the gap tends to be less likely to occur. In addition, the content of the inorganic filler (C) in the epoxy resin composition is also easily adjusted, and the cured product tends to exhibit high toughness.

[0039] Examples of the coupling agent include silane coupling agents having an epoxy group such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 8-glycidoxyoctyltrimethoxysilane; silane coupling agents having a (meth)acryloyl group such as 3-methacryloxypropyltrimethoxysilane and 8-methacryloxyoctyltrimethoxysilane; and silane coupling agents having a substituted or unsubstituted amino group (particularly a phenylamino group) such as N-phenyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltriethoxysilane. As the surface treatment for the inorganic filler (C), the above coupling agents can be used alone or in combination of two or more.

[0040] The shape of the inorganic filler (C) is not particularly limited, but examples thereof include a spherical shape (such as a true spherical shape or a nearly true spherical shape), a polyhedral shape, a rod shape (such as a cylindrical shape or a prismatic shape), a flat plate shape, a scale shape, and an irregular shape. Among these, a spherical shape is preferable from the viewpoint of increasing the loading amount.

[0041] The average particle size of the inorganic filler (C) is not particularly limited, but is, for example, preferably 1 nm to 8 μm, more preferably 3 nm to 5 μm, even more preferably 0.05 to 4 μm, particularly preferably 0.1 to 3.5 μm, and most preferably 0.3 to 3 μm. When the average particle size of the inorganic filler (C) is within the above range, the epoxy resin composition has an appropriate viscosity, and the problem of a decrease in speed during injection into a gap is unlikely to occur.

[0042] The method for measuring the average particle size of the inorganic filler (C) is not particularly limited, but it can be measured using a laser diffraction / scattering particle size distribution analyzer (product name: LS 13 320, manufactured by Beckman Coulter). In this case, the average particle size of the inorganic filler means the volume average particle size D50 (particle size that is 50% cumulative from the small diameter side of the particle size distribution). The actual measurement is performed under the conditions of a flow rate of 50 ml / sec, a measurement time of 90 seconds, pure water as the solvent, and a solvent refractive index of 1.333, by mixing 5 mg of the inorganic filler with 50 mg of a dispersant (sodium hexametaphosphate) and dispersing the sample for 10 minutes using an ultrasonic disperser.

[0043] In the present invention, when the inorganic filler (C) contains an inorganic filler (C-1) having an average particle size of 1 to 100 nm and an inorganic filler (C-2) having an average particle size of 0.2 to 8 μm, it is preferable in that the problem of speed reduction is unlikely to occur, especially when injecting into a gap. The reason for this is considered to be that when two or more inorganic fillers having different average particle sizes are used in combination, the epoxy resin composition approaches a close-packed state, which further reduces the viscosity. The inorganic filler (C-1) has an average particle size of more preferably 3 to 40 nm, and even more preferably 6 to 15 nm. The inorganic filler (C-2) has an average particle size of preferably 0.3 to 5 μm, and even more preferably 0.5 to 3 μm.

[0044] The content of the inorganic filler (C) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more. Also, it is preferably 80% by mass or less, more preferably 75% by mass or less, and preferably 70% by mass or less. When the content of the inorganic filler (C) is within the above range, the thermal expansion of the cured product tends to be reduced and the toughness tends to be improved. Also, the viscosity of the epoxy resin composition tends to be reduced.

[0045] [Cellulose nanofiber (D)] The cellulose nanofiber (D) is not particularly limited, but may refer to, for example, cellulose fibers produced by mechanically defibrating and refining plant fibers, the average fiber width of which is nanoscale. Before or after the mechanical treatment, chemical or enzymatic treatment may be carried out as necessary. The cellulose nanofiber (D) is dispersed in a mesh-like form in the cured product to form a network structure, thereby imparting high toughness to the cured product. Furthermore, it suppresses the thermal deformation of the cured product and reduces thermal expansion.

[0046] The raw material for the plant fibers is not particularly limited, and examples thereof include wood-based pulps such as coniferous pulp and broadleaf pulp, cotton-based pulps such as cotton lint and cotton linter, non-wood pulps such as wheat straw and bagasse, plant-derived cellulose, animal-derived cellulose, bacterial nanocellulose, and the like.

[0047] The cellulose nanofibers (D) may be hydrophilic, but are preferably hydrophobic. This is because hydrophobic cellulose nanofibers have a smaller tendency to aggregate or precipitate in epoxy resins or epoxy resin compositions than hydrophilic cellulose nanofibers. In other words, from the viewpoint of compatibility and dispersibility with epoxy resins, the cellulose nanofibers (D) are preferably hydrophobized cellulose nanofibers (sometimes referred to as "hydrophobized cellulose nanofibers").

[0048] Generally, cellulose is hydrophilic because it has many hydroxyl groups. In addition, cellulose that is more defibrated and finely divided while maintaining its hydrophilicity can be produced by a method of introducing an aldehyde group or a carboxyl group by oxidation, a method of introducing a carboxymethyl group into the hydroxyl group, or a method of substituting a phosphate group, a phosphite group, or a sulfo group for the hydroxyl group. The reason for this can be explained as follows. By introducing an aldehyde group, a carboxyl group, a phosphate group, a phosphite group, or a sulfo group into cellulose, a repulsive force due to these functional groups is generated between cellulose molecules. The generation of a repulsive force between cellulose molecules makes it possible to easily produce cellulose nanofibers with a small fiber width (average fiber width) by mechanical processing.

[0049] Cellulose nanofibers made of such hydrophilic cellulose are referred to as hydrophilic cellulose nanofibers. As described above, examples of hydrophilic cellulose nanofibers include cellulose nanofibers that have not been chemically or enzymatically modified, cellulose nanofibers into which aldehyde groups have been introduced (aldehyde group-introduced cellulose nanofibers), cellulose nanofibers into which carboxy groups have been introduced (carboxy group-introduced cellulose nanofibers), cellulose nanofibers into which phosphate groups have been introduced (phosphate group-introduced cellulose nanofibers), cellulose nanofibers into which phosphite groups have been introduced (phosphite group-introduced cellulose nanofibers), and cellulose nanofibers into which sulfo groups have been introduced (sulfo group-introduced cellulose nanofibers), but are not particularly limited thereto.

[0050] The method of imparting hydrophobicity to cellulose nanofibers to produce hydrophobized cellulose nanofibers is not particularly limited, but examples include (1) a method of esterifying some of the hydroxyl groups of cellulose nanofibers with carboxylic acids or carboxylic anhydrides to produce cellulose nanofibers to which hydrocarbon groups are bonded via ester bonds, (2) a method of reacting the above-mentioned aldehyde group-introduced cellulose nanofibers or carboxyl group-introduced cellulose nanofibers with a hydrocarbon group-containing compound such as an alcohol or an amine compound to produce cellulose nanofibers to which hydrocarbon groups are bonded via ester bonds or cellulose nanofibers to which hydrocarbon groups are bonded via amide bonds, and (3) a method of reacting a halogenated cellulose nanofiber or a cellulose nanofiber to which an acid halide group has been introduced with a hydrocarbon group-containing compound such as a compound having an aryl group to produce cellulose nanofibers in which hydroxyl groups have been replaced with hydrocarbon groups. That is, examples of hydrophobized cellulose nanofibers include hydrocarbon group-introduced cellulose nanofibers such as the above-mentioned cellulose nanofibers to which hydrocarbon groups are bonded via ester bonds, the above-mentioned cellulose nanofibers to which hydrocarbon groups are bonded via amide bonds, and the above-mentioned cellulose nanofibers in which hydroxyl groups have been replaced with hydrocarbon groups. In addition, when plant fibers are defibrated by mechanical processing, a direct pulp kneading method or an underwater counter collision (ACC) method is used to obtain hydrophobic cellulose nanofibers. The direct pulp kneading method is a method in which plant fibers (cellulose) are hydrophobized and then defibrated and refined to obtain cellulose nanofibers. The underwater counter collision (ACC) method is a method in which the hydrophobic surface of the cellulose nanofiber appears on the surface when plant fibers (cellulose) are defibrated and refined. Such hydrophobic cellulose nanofibers have high compatibility with epoxy resins and can suppress aggregation and precipitation in epoxy resins and epoxy resin compositions, so that both low thermal expansion and high toughness tend to be improved.

[0051] In the cellulose nanofibers into which a hydrocarbon group has been introduced, the hydrocarbon group to be introduced is not particularly limited. The hydrocarbon group may be an aliphatic hydrocarbon group or an aromatic hydrocarbon group, and if it is an aliphatic hydrocarbon group, it may be a linear, branched, or cyclic hydrocarbon group. The number of carbon atoms in the hydrocarbon group is not particularly limited, but is 1 to 30.

[0052] The cellulose nanofiber (D) may be used alone or in combination of two or more kinds. The cellulose nanofiber (D) may be made into a master batch with a resin material such as an epoxy resin.

[0053] When a hydrocarbon group is introduced into the cellulose nanofiber (D), the amount of the introduced group is not particularly limited, but is preferably 0.01 to 10 mmol / g, more preferably 0.1 to 3 mmol / g, and even more preferably 0.3 to 1 mmol / g. The number of carbon atoms in the hydrocarbon group is not particularly limited, and is selected as desired depending on the combination with a curable resin such as an epoxy resin.

[0054] The average fiber width of the cellulose nanofiber (D) is not particularly limited, but is preferably 1 to 1000 nm, more preferably 3 to 500 nm, and even more preferably 3 to 100 nm. When the average fiber width of the cellulose nanofiber (D) is within the above range, the cellulose nanofiber filling rate in the cured product becomes an appropriate value, and a network structure of the cellulose nanofiber is easily formed, so that the thermal expansion tends to be further reduced. The average fiber length of the cellulose nanofiber (D) is not particularly limited, but is preferably, for example, 0.5 to 100 μm, and more preferably 1 to 50 μm. The aspect ratio of the cellulose nanofiber (D) is not particularly limited, but is preferably, for example, 10 or more, and more preferably 20 or more. In addition, the aspect ratio is not particularly limited, but is preferably, for example, 2000 or less, and more preferably 1000 or less.

[0055] The method for calculating the average fiber width and average fiber length of the cellulose nanofibers (D) is not particularly limited, but for example, the fiber width and fiber length of a sufficient amount of fibers are measured using an atomic force microscope (AFM) or a transmission electron microscope (TEM) and these values ​​are averaged to calculate the aspect ratio. The aspect ratio is the average fiber width divided by the average fiber length (average fiber length / average fiber width).

[0056] The content of the cellulose nanofibers (D) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is preferably 0.1 to 10.0% by mass, more preferably 0.1% by mass or more and less than 5% by mass, even more preferably 0.2 to 3% by mass, and particularly preferably 0.2 to 1% by mass. When the content of the cellulose nanofibers (D) is within the above range, the epoxy resin composition has an appropriate viscosity, and the thermal expansion of the cured product tends to be reduced and the toughness tends to be improved. In particular, when the content of the cellulose nanofibers (D) is less than 5% by mass, the viscosity of the epoxy resin composition is further reduced, and the problem of speed reduction during injection into a gap tends to be less likely to occur.

[0057] [Reactive diluent (E)] The epoxy resin composition of the present invention may further contain a reactive diluent (E). The reactive diluent (E) is not particularly limited as long as it has reactivity and reduces the viscosity of the epoxy resin composition. Examples of the reactive diluent (E) include compounds containing an epoxy group and having a molecular weight of 350 or less. The reactive diluent (E) may be used alone or in combination of two or more.

[0058] Examples of the reactive diluent (E) include 1,4-cyclohexanedimethanol diglycidyl ether, 1,2-epoxy-4-(2-methyloxiranyl)-1-methylcyclohexane, 4-tert-butylphenyl glycidyl ether, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, neodecanoic acid glycidyl ester, and glycidylaniline type epoxy resins (for example, trade names GAN and GOT, both manufactured by Nippon Kayaku Co., Ltd.).

[0059] The content of the reactive diluent (E) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is, for example, preferably 0.1 to 10.0% by mass, more preferably 0.5 to 6% by mass, and particularly preferably 1 to 4% by mass. By having the content of the reactive diluent (E) within the above range, the epoxy resin composition has an appropriate viscosity, and the thermal expansion of the cured product tends to be reduced, and the toughness tends to be improved.

[0060] [Other ingredients] The epoxy resin composition of the present invention may contain components other than the epoxy resin (A), the curing agent (B), the inorganic filler (C), the cellulose nanofiber (D), and the reactive diluent (E) (hereinafter referred to as "other components (F)"). Examples of the other components (F) include curable compounds other than the epoxy resin (A) and the reactive diluent (E), inorganic fillers that have not been surface-treated, thermoplastic resins such as polyethylene resins, polyester resins, polyurethane resins, and polyamide resins, coupling agents (e.g., silane coupling agents), ion trapping agents, leveling agents, antioxidants, defoamers, flame retardants, colorants, solvents, elastomers, etc. The other components (F) may be used alone or in combination of two or more.

[0061] The content of the other component (F) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited as long as it does not impair the effects of the present invention, but is, for example, preferably 0.001 to 10% by mass, more preferably 0.01 to 5% by mass, and even more preferably 0.1 to 3% by mass. Among these, the content of the coupling agent (e.g., silane coupling agent) relative to the epoxy resin composition of the present invention (100% by mass) is, for example, preferably 1% by mass or less, more preferably 0.04% by mass or less, and even more preferably 0.01% by mass or less.

[0062] In the epoxy resin composition of the present invention, the inorganic filler that has not been surface-treated may be used in place of the inorganic filler (C-1) or the inorganic filler (C-2). That is, the epoxy resin composition of the present invention may include an embodiment that contains an inorganic filler (C-1) having an average particle size of 1 to 100 nm and an inorganic filler that has not been surface-treated and has an average particle size of 0.2 to 8 μm, or an embodiment that contains an inorganic filler that has an average particle size of 1 to 100 nm and an inorganic filler (C-2) having an average particle size of 0.2 to 8 μm.

[0063] The content of the other component (F) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited as long as it does not impair the effects of the present invention, but is, for example, preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. Also, for example, it is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more.

[0064] [Physical properties and production method of epoxy resin composition] The viscosity of the epoxy resin composition of the present invention (25°C, Brookfield viscometer, 50 rpm) is not particularly limited, but is, for example, preferably 0.1 to 300 Pa s, more preferably 1 to 80 Pa, still more preferably 5 to 60 Pa s, and particularly preferably 12 to 40 Pa s. When the viscosity is within the above range, injection into gaps tends to be easier.

[0065] The epoxy resin composition of the present invention can be prepared by a known and commonly used method. For example, the epoxy resin (A), the curing agent (B), the inorganic filler (C), and the cellulose nanofiber (D), as well as the reactive diluent (E) and other components (F) as required, are simultaneously or separately introduced into an appropriate mixer, and stirred and mixed while melting by heating as required, to obtain the epoxy resin composition of the present invention. When the epoxy resin (A) is solid, it is preferable to heat it to liquefy or fluidize it before mixing. When it is difficult to uniformly disperse the inorganic filler (C) in the epoxy resin composition, the epoxy resin and the inorganic filler (C) may be heated and mixed to uniformly disperse the inorganic filler (C) in the epoxy resin, and then cooled as required, and further components such as the curing agent (B) may be mixed to prepare the epoxy resin composition of the present invention.

[0066] The mixer is not particularly limited, and examples thereof include a roll mill equipped with a stirrer and a heater, a Raikai mixer, a Henschel mixer, a tumbler, a planetary mixer, etc. The mixing ratio of each component is appropriately set according to the content of each component in the epoxy resin composition.

[0067] The epoxy resin composition of the present invention can be preferably used as a material for sealing a semiconductor element arranged on a substrate in a semiconductor device (an epoxy resin composition for semiconductor sealing). By using the epoxy resin composition of the present invention as an epoxy resin composition for semiconductor sealing, a sealed body having excellent thermal cycle resistance can be produced. The epoxy resin composition of the present invention can also be preferably used as a material for sealing a semiconductor element arranged on a substrate in a flip-chip type semiconductor device (an epoxy resin composition for flip-chip type semiconductor sealing). Specifically, the epoxy resin composition of the present invention is injected into the gap between a semiconductor element and a substrate and subjected to thermal curing, thereby sealing the bump electrodes present in the gap and fixing the semiconductor element and the substrate to each other as a sealed body, thereby improving thermal cycle resistance.

[0068] Examples of the epoxy resin composition for semiconductor encapsulation include underfills such as capillary underfill, liquid mold underfill, secondary underfill, and pre-applied underfill, as well as grab top materials and liquid compression molding materials. The epoxy resin composition of the present invention is not limited to the above-mentioned use as an epoxy resin composition for semiconductor encapsulation, and can be used, for example, as an adhesive for fixing, joining, or protecting components constituting electronic components.

[0069] [Cured product] A cured product is formed by curing the epoxy resin composition of the present invention. The curing method is not particularly limited, but for example, the epoxy resin composition is subjected to a heat treatment. The heat treatment temperature is not particularly limited, but for example, 60 to 200°C is preferable, and 80 to 180°C is more preferable. The heat treatment time is not particularly limited, but for example, 0.1 to 5 hours is preferable, and 0.5 to 3 hours is more preferable.

[0070] The fracture toughness of the cured product is not particularly limited, but is, for example, 1.5 MPa m 1 / 2 It is preferable that the viscosity is equal to or higher than 1.8 MPa m. 1 / 2 More preferably, 2.0 MPa m 1 / 2 More than 2.5 MPa m is especially preferable. 1 / 2 More than 3.0MPa m, most preferably 3.0MPa m 1 / 2 The fracture toughness of the cured product is not particularly limited, but is, for example, 20 MPa m 1 / 2 The fracture toughness is within the above range, so that the thermal cycle resistance tends to be further improved. The fracture toughness can be measured, for example, by the method described in the Examples.

[0071] The linear expansion coefficient of the cured product is not particularly limited, but is preferably 30 ppm / °C or less, more preferably 29 ppm / °C or less, and even more preferably 28 ppm / °C or less. The linear expansion coefficient of the cured product is not particularly limited, but is, for example, 1 ppm / °C or more. When the linear expansion coefficient is within the above range, the thermal cycle resistance tends to be further improved. The linear expansion coefficient can be measured, for example, by the method described in the examples.

[0072] <Semiconductor device> The semiconductor device of the present invention comprises a substrate, a semiconductor element disposed on the substrate, and a cured product of the epoxy resin composition of the present invention that encapsulates the semiconductor element. The semiconductor device is preferably a flip-chip type semiconductor device. The flip-chip type semiconductor device has a structure in which an electrode portion on a substrate and a semiconductor element are connected via a bump electrode. In the semiconductor device, the gap between the semiconductor element and the substrate is encapsulated with a cured product (encapsulant) of the epoxy resin composition of the present invention.

[0073] The epoxy resin composition of the present invention is injected into the gap between the semiconductor element and the substrate, and then thermally cured to form a sealing body (cured product). The method of injecting the epoxy resin composition of the present invention into the gap is not particularly limited, but for example, the epoxy resin composition is applied to one end of the substrate or the semiconductor element while heating the substrate to 50 to 120°C, and the epoxy resin composition is filled into the gap between the substrate and the semiconductor element by capillary action. After filling the gap with the epoxy resin composition of the present invention, the substrate is heated at a predetermined temperature for a predetermined time, specifically, at the temperature and time described in the heat treatment for forming the cured product, to seal the gap. EXAMPLES

[0074] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0075] The epoxy resin compositions of Examples 1 to 15 and Comparative Examples 1 to 3 were prepared by appropriately selecting and mixing the epoxy resin (A), curing agent (B), inorganic filler (C), cellulose nanofiber (D), and reactive diluent (E) according to the blending ratio shown in Table 1. The numerical values ​​for each component in Table 1 represent parts by mass.

[0076] Each component in Table 1 will be explained below. Epoxy resin (A) EXA 835LV (product name): Bisphenol F type epoxy resin, epoxy equivalent 156-170g / eq, liquid at 25℃, manufactured by DIC Corporation jER630 (product name): Aminophenol type epoxy resin, epoxy equivalent 98g / eq, liquid at 25℃, manufactured by Mitsubishi Chemical Corporation EP3980S (product name): Glycidylamine type epoxy resin, epoxy equivalent 115g / eq, liquid at 25℃, manufactured by ADEKA Corporation YX7400N (product name): Polyalkylene glycol type epoxy resin, epoxy equivalent 400-500g / eq, liquid at 25℃, manufactured by Mitsubishi Chemical Corporation Hardener (B) KAYAHARD AA (product name): Amine-based hardener, 4,4'-diamino-3,3'-diethyldiphenylmethane, equivalent weight 64g / eq, manufactured by Nippon Kayaku Co., Ltd. HN2200 (product name): Acid anhydride curing agent, 3 or 4-methyl-1,2,3,6-tetrahydrophthalic anhydride, equivalent weight 82 to 84 g / eq, manufactured by Resonac Co., Ltd. MEH-8005 (product name): Phenol-based hardener, equivalent weight 133-138g / eq, manufactured by Meiwa Chemical Industry Co., Ltd. 2P4MZ (product name): Imidazole-based curing agent, 2-phenyl-4-methylimidazole, manufactured by Shikoku Kasei Co., Ltd. ·Inorganic filler (C) SE605H-SMG (product name): Silica with average particle size of 2 μm, surface-treated with 3-methacryloxypropyltrimethoxysilane, manufactured by Admatechs Co., Ltd. 20SX-E7 (product name): Silica with average particle size of 2 μm, surface-treated with N-phenyl-3-aminopropyltrimethoxysilane, manufactured by Admatechs Co., Ltd. 20SE-E10 (product name): Silica with average particle size of 2 μm, surface-treated with 3-glycidoxypropyltrimethoxysilane, manufactured by Admatechs Co., Ltd. SE5200-SME (product name): Average particle size 1.5 μm, silica surface-treated with 3-methacryloxypropyltrimethoxysilane, manufactured by Admatechs Co., Ltd. YA010AJGP (product name): Masterbatch of nano-silica with an average particle size of 10 nm and bisphenol F type epoxy resin (weight ratio of the former to the latter = 3:7), nano-silica surface-treated with 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, manufactured by Admatechs Co., Ltd.) Other inorganic fillers SO-E5 (product name): average particle size 1.3 to 1.7 μm, surface untreated silica, manufactured by Admatechs Co., Ltd.) Cellulose nanofiber (D) CNF1: Hydrophobized cellulose nanofiber with an average fiber width of 3 nm CNF2: Hydrophobized cellulose nanofiber with an average fiber width of 50 nm CNF3: Hydrophobized cellulose nanofiber with an average fiber width of 100 nm CNF4: Hydrophobized cellulose nanofiber with an average fiber width of 500 nm CNF5: Hydrophilic cellulose nanofiber with an average fiber width of 3 nm CNF1 to 4 are cellulose nanofibers in which hydrocarbon groups are bonded via amide bonds. ·Reactive diluent (E) ZX-1658GS (product name): 1,4-cyclohexanedimethanol diglycidyl ether, manufactured by Nippon Steel Chemical & Material Co., Ltd.

[0077] (Evaluation 1: Viscosity and TI measurements) The viscosity (initial viscosity, unit: Pa s) immediately after preparation of the epoxy resin compositions of Examples 1 to 15 and Comparative Examples 1 to 3 was measured using a Brookfield viscometer (model number: HBDV-1, manufactured by Brookfield) at a liquid temperature of 25°C and rotated at 50 rpm for 1 minute. The results are shown in the "Viscosity" section of the evaluation results in Table 1. The viscosities were also measured at 50 rpm and 5 rpm in the same manner as above, and the thixotropic index (TI: viscosity at 5 rpm / viscosity at 50 rpm) was calculated from the values. The results are shown in the "TI" section of the evaluation results in Table 1.

[0078] (Evaluation 2: Measurement of fracture toughness) The epoxy resin compositions of Examples 1 to 15 and Comparative Examples 1 to 3 were cured at 165°C for 120 minutes to prepare test pieces measuring 75 mm in length × 14 mm in width × 7 mm in thickness. A crack was introduced in the thickness direction at the center of the longitudinal direction of the test pieces with a razor. The notch depth was 6.7 to 7.3 mm, and the pre-crack was 0.7 to 1.0 mm. The initial crack length was measured at 5 points up to 0.01 mm using a 50x reading microscope and averaged. The test pieces were used to measure the fracture toughness (MPa m) in accordance with ASTM D-5045-91 (Standard Test Methods for Plane-Strain Fracture Toughness and Strain Energy Release Rate of Plastic Materials) using a Shimadzu Autograph AG-IS (manufactured by Shimadzu Corporation). 1 / 2 The results are shown in the "Fracture Toughness" section of the evaluation results in Table 1.

[0079] (Evaluation 3: Measurement of linear expansion coefficient) The epoxy resin compositions of Examples 1 to 15 and Comparative Examples 1 to 3 were cured at 165°C for 120 minutes to obtain cured products, which were then subjected to measurement of linear expansion coefficients (ppm / °C) at 0 to 20°C using a Bruker ASX TMA4000SA series in accordance with the method described in JIS K 7197-1991, except that (1) test piece size was 8 mm in diameter x 20 mm in height, (2) measurement mode: compression, and (3) heating rate: 5°C / min. The results are shown in the "linear expansion coefficient" column of the evaluation results in Table 1.

[0080] [Table 1]

Claims

1. Epoxy resin (A), A curing agent (B), A surface-treated inorganic filler (C), and Cellulose nanofiber (D), 1. An epoxy resin composition comprising:

2. The epoxy resin composition according to claim 1, wherein the cellulose nanofibers (D) have an average fiber width of 1 to 1000 nm.

3. The epoxy resin composition according to claim 1 or 2, wherein the cellulose nanofiber (D) is a hydrophobized cellulose nanofiber.

4. 3. The epoxy resin composition according to claim 1, wherein the inorganic filler (C) has an epoxy group, a (meth)acryloyl group, or a substituted or unsubstituted amino group.

5. 3. The epoxy resin composition according to claim 1, wherein the inorganic filler (C) comprises an inorganic filler (C-1) having an average particle size of 1 to 100 nm and an inorganic filler (C-2) having an average particle size of 0.2 to 8 μm.

6. The epoxy resin composition according to claim 1 or 2, wherein the content of the cellulose nanofibers (D) is 0.1 to 10.0 mass% relative to the epoxy resin composition (100 mass%).

7. The epoxy resin composition according to claim 1 or 2, further comprising a reactive diluent (E).

8. 3. The epoxy resin composition according to claim 1, having a viscosity at 25° C. of 1 to 80 Pa·s.

9. 3. The epoxy resin composition according to claim 1, which is used for encapsulating a semiconductor.

10. A cured product of the epoxy resin composition according to claim 1 or 2.

11. A semiconductor device comprising: a substrate; a semiconductor element disposed on the substrate; and the cured product according to claim 10 that seals the semiconductor element.

Citation Information

Patent Citations

  • Liquid epoxy resin sealing material

    JP2000336247A

  • Liquid epoxy resin composition for sealing semiconductor having controlled flowability

    JP2009185188A

  • Semiconductor device and method of manufacturing the same

    JP2010192525A

  • Organized fiber, resin composition, and method for producing the resin composition

    JP2011047084A

  • Epoxy resin composition, semiconductor sealant and semiconductor device

    JP2015105304A